Video 2_Doxorubicin induces cardiotoxicity by enhancing autophagy via mTOR signaling in hiPSC- and hESC-derived cardiomyocytes.mp4 - Minxia Ke (4889887) (2025)
Introduction Doxorubicin (DOX) is a highly effective anti-cancer drug, but its clinical applications are limited by its cardiotoxicity. The mechanisms underlying DOX-induced cardiotoxicity (DIC) remain incompletely understood. Human induced pluripotent stem cells (hiPSCs) and human embryonic stem cells (hESCs) offer an advanced platform for investigating DIC, as they accurately recapitulate human cardiac physiology and pathology. However, the roles and mechanisms of DIC in hiPSC-CMs and hESC-CMs, especially regarding autophagy dynamics and regulation, are still not well-defined. Methods Cell viability, apoptosis, reactive oxygen species production, and DNA damage were assessed. Autophagy was evaluated by transmission electron microscope, LC3-II/LC3-I ratio, and autophagy flux assays. The role of autophagy and mTOR signaling was investigated using 3-methyladenine (3-MA) and rapamycin (RAPA), respectively. Results DOX reduced cell viability and induced apoptosis in hiPSC-CMs and hESC-CMs. Additionally, DOX caused an increase in reactive oxygen species production and DNA damage. Furthermore, DOX significantly upregulated autophagy, confirmed by the accumulation of autophagosomes and autolysosomes, and an increase in the LC3-II/LC3-I ratio. Autophagy flux assays showed that DOX induced autophagy in a time-dependent manner. The autophagy mediated by DOX was partially attenuated by 3-MA. Moreover, this activation was due to mTOR signaling inhibition. The downregulation of mTOR signaling by RAPA increased cell death of hESC-CMs. Interestingly, minor variations in injury severity and cellular sensitivity were observed between these two models. Conclusion Our study uncovered the multifaceted effects of DOX on hiPSC-CMs and hESC-CMs, revealing a shared mechanism in which DOX enhances autophagy via inhibition of the mTOR signaling pathway. These findings reveal key insights into DIC pathogenesis and suggest that autophagy modulation may be a promising therapeutic strategy.